2021 IEEE International Conference on Omni-Layer Intelligent Systems (COINS) 2021
DOI: 10.1109/coins51742.2021.9524172
|View full text |Cite
|
Sign up to set email alerts
|

A Decentralised Authentication and Access Control Mechanism for Medical Wearable Sensors Data

Abstract: Recent years have seen an increase in medical big data, which can be attributed to a paradigm shift experienced in medical data sharing induced by the growth of medical technology and the Internet of Things. The evidence of this potential has been proved during the recent covid-19 pandemic, which was characterised by the use of medical wearable devices to help with the medical data exchange between the healthcare providers and patients in a bid to contain the pandemic. However, the use of these technologies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Storing data in the public cloud increases security and privacy concerns. If there is a single failure, a third party needs to handle or solve such issues, which can lead to the leakage of health data [104].…”
Section: Cloud Server Security Risksmentioning
confidence: 99%
“…Storing data in the public cloud increases security and privacy concerns. If there is a single failure, a third party needs to handle or solve such issues, which can lead to the leakage of health data [104].…”
Section: Cloud Server Security Risksmentioning
confidence: 99%
“…The technology has the ability to change the future direction of businesses, with studies indicating a proliferation of research in the practical uses of blockchain technology that go far beyond its common application in the finance sector and cryptocurrency, where the technology is most widely used [10]. Research papers have identified opportunities within healthcare [11], [12], [13], supply chain resilience [14], authentication and access control [15] and internet of things (IoT) integration [16], [17] amongst other sectors. One emerging blockchain technology application area which has experienced high levels of success are NFTs, which have been increasingly adopted to certify the ownership, traceability and authenticity of a digital or physical asset [18].…”
Section: Blockchain Technology Applicationsmentioning
confidence: 99%